REFLEXIVE APPROACH IN BUSINESS, MANAGEMENT, ECONOMICS, AND MARKETING: INFORMATION SUPPORT FOR THE EFFICIENCY OF BUSINESS PROCESSES - KUCHER, Anatolii; KUCHER, Lesia; ANTOSHCHENKOVA, Vitalina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article presents the results of a theoretical analysis of the essence of reflexive management and a bibliometric analysis of studies on the application of a reflexive approach in various areas, with an emphasis on business, management, economics and marketing, as a theoretical basis for the development of information support for the effectiveness of business processes. Using the VOSviewer software and metadata from the Scopus database, two bibliometric maps of the most used terms were constructed: the first – in publications on the application of the reflexive approach, includes 437 keywords that were used at least five times, combined into eight thematically related clusters; the second – in publications on the application of a reflexive approach in the field of business, management, economics and marketing, includes 44 keywords that were used at least three times, combined into nine clusters.The results of cluster analysis and analysis of documents by fields of knowledge collectively indicate the interdisciplinary nature of research on the application of the reflexive approach in the world and the understanding of this phenomenon primarily in the aspect of social and behavioral sciences. In general, economic sciences accounted for 13.3% of the global volume of publications. The leaders in terms of the number of studies on the reflexive approach among countries, organizations and authors have been identified. Five clusters of countries were identified according to the level of cooperation on the researched issue. A bibliometric landscape has been formed regarding the application of a reflexive approach in business, management, economics, and marketing as a theoretical basis for the development of information support for the effectiveness of business processes.
Keywords: reflection; reflective management; management of business processes based on a reflexive approach; information support; personnel management; management of agricultural enterprises; sustainable management of agricultural nature use